Grado de satisfacción con la simulación y prácticas docentes tradicionales en la adquisición de competencias clínicas en Semiología Neurológica en estudiantes de la Titulación de Médico de la Universidad Técnica Particular de Loja. Septiembre 2012- Febrero 2013. - Buele Banegas, Giovanni Andrés (2014)
This research is performed in order to compare two methods of teaching students and teachers in the Degree of Doctor for the acquisition of clinical skills in analyzing neurological involvement satisfaction. The study was descriptive, prospective, comparative, cross-type focus and quantitative design. The population consisted of seventh and ninth cycle, as well as teachers of neurological involvement. The survey instrument was applied. The results show that the traditional teaching methodology leaves dissatisfied students with a mean Likert scale of 2.43 / 5, and teachers satisfied with 3.15 / 5. With simulation workshops, both students (4.70 / 5) and teachers (4.60 / 5) were found very satisfied. As for the advantages and disadvantages of 83.33% teachers reported greater acceptance by the simulation as a more efficient methodology, and advantages over traditional. In conclusion, the teaching of neurological involvement through clinical simulation shows a high degree of satisfaction among students and teachers in relation to the traditional methodology.